PERANCANGAN VIDEO SENTRA INDUSTRI KERUPUK PULI DI KAMPUNG KEDUNG REJO SEBAGAI UPAYA UNTUK MENGENALKAN KEPADA MASYARAKAT - Fernanda, Vicky Regiansyah; Martono, Siswo; Prasetya, Ardian Jaya (Jurnal Art Nouveau, 2018)
Kedung Rejo is a cracker village Sidoarjo in Jabon village. The kind of business in the village is crackers maker, and then this village can call the craker village. But just only certain people knows about the village because Kedung Rejo cracker village is not expose and away from highway. But access for go in the Kedung Rejo cracker village is to easy.The cracker maker in Kedung Rejo village was available since 1985, and at the time many people in Kedung Rejo village is cracker maker and the kind of cracker can call puli. Mrs Juwariyah as Head of Economic Division in Jabon said, is many people don’t know about Kedung Rejo village wich has UKM center puli cracker. This is because people in Kedung Rejo village less focusing it market share to the general public and more to market it to the distributor of crackers and traditional markets, while Mrs Juwariyah hope is not only the distributor of crackers and the market but also the general public too. From the problem, need to make the video center of puli cracker industri in Kedung Rejo village as an effort to introduce for the people.